ACCESSIBILITY FOR DIFABLED ON PUBLIC SPACE IN SIMPANG LIMA SEMARANG, INDONESIA - Kurniati, Rina; Almas, Dhafina (Science and Technology Research Centre, Universitas PGRI Semarang, 2020)
Simpang Lima is a CBD of Semarang City that has a high level of activity. Improvements have been made to the faces of the Simpang Lima area and included the provision of facilities for difabled, but not yet many difabled persons accessing the area due to difficult access to and from the area. This research aims to assess the accessibility of difable to public open space in Simpang Lima area by analyzing the application of public facilities, especially for difabled and analyzing alternative solutions in the provision of accessible public facilities based on difabled needs. The Data acquired by distributing questioner to the difabled who are members of the â€œKomunitas Sahabat Difabelâ€ and the audit of difable facilities in Simpang Lima area based on the provision of facilities. Based on the research conducted, it is known that the accessibility in Simpang Lima Semarang area for difabled is still less accessible with the final value of 1.97 from the scale of 1 to 3. This is due to the incomplete disfigured facilities in the area as well as some facilities already available but not in accordance with the provision of difabled facilities. In addition, in this study also produce the direction of planning the area such us, connecting the guiding block there is disconnected, increasing the number of ram at each height different and on each entrance, the supply of crossing lights, the addition of signage especially for difabled, and the addition of other difabled facilities such as parking areas and toilets specially for difabled persons.